The invasion potential of selected Berberis species in South Africa - Keet, Jan-Hendrik (University of the Free State, 2015)
Invasive alien species are a serious threat to global biodiversity. They have considerable negative effects on the economy and the environment, using up valuable natural and monetary resources. Every year new species are introduced into South Africa and with that the list of potentially new invasive species grows. These emergent invasive species should receive a very high priority in terms of assessing their invasion potential and possible impacts. No formal study has been conducted regarding the invasion potential of any species in the genus Berberis within South Africa, even though it has been a popular horticultural genus for many decades and is known to have invasive species. The current study focussed on four key points, namely: 1) the elucidation of all Berberis spp. that have been historically and are currently cultivated within South Africa, 2) assessing the size, extent and reproductive age of any naturalized/invasive Berberis populations, 3) determining potential habitable areas of naturalized/invasive Berberis species and 4) determining whether any Berberis species should be officially listed under the National EnvironmentalManagement Biodiversity Act. A total of 30 Berberis species/cultivars/hybrids were found to have been cultivated in South Africa in the past and present (11 species, 11 cultivars, 8 hybrids). Three of these species are widespread invasives in other parts of the world, namely B. darwinii, B. thunbergii and B. vulgaris. The KwaZulu-Natal Province has the highest diversity of species/cultivars/hybrids stocked by nurseries/private/wholesale growers, while B. thunbergii and B. thunbergii var. atropurpurea were found to be the most widely stocked species. Two invasive Berberis populations were found. The first population was from the species Berberis aristata and occurs in the Woodbush State Forest (Limpopo Province; 23.8192°S 29.9608°E). This population has an extent of occurrence of 115 ha and an area of occupancy of 1.58 ha. A total of 5 725 individuals were geotagged and the population was found to be highly reproductively active, with more than 40% of the population able to flower and set seed. The second population was from the species B. julianae and occurs at the Glen Reenen rest camp in the Golden Gate Highlands National Park (Free State Province; 28.5049°S 28.6187°E). This population has an extent of occurrence of 0.42 ha and an area of occupancy of 0.02 ha. It was also found to be highly reproductively active with 38% of the population able to flower and set seed. A few minor occurrences of this species were found at the Alma Ranger Station, also in the Golden Gate Highlands National Park. A total of 473 individuals of this species were geotagged. Bioclimatic modelling revealed that substantial parts of South Africa are suitable for both Berberis aristata and B. julianae. The former species was found to be more suitable to the mountainous regions while the latter has a higher suitability to the central parts of the country. The situation regarding future climate scenarios (2020) was the same, although a range contraction was found for both species. Weed risk assessments revealed that both B. aristata and B. julianae would have failed a pre-border screening (score of 27 and 22, respectively, according to the Australian Weed Risk Assessment system), indicating that both species pose an environmental risk. Herbicide trial clearing revealed that three chemicals can be used for the successful control of Berberis spp., namely metsulfuron-methyl, triclopyr and glyphosate. The final outcome of the study is the following recommendations: Berberis aristata should be listed as a category 1a invasive species in the National Environmental Management Biodiversity Act, while B. julianae should be listed as category 1b in non-urban areas and not listed in urban areas.

Uitheemse indringer plante is ‘n ernstige bedreiging vir wêreldwye biodiversiteit. Hulle het aansienlike negatiewe effekte op die ekonomie en die omgewing en gebruik waardevolle natuurlike en geldelike hulpbronne. Nuwe spesies word elke jaar in Suid-Afrika ingevoer en veroorsaak dat die lys van potensiële nuwe indringer spesies ook groei. Hierdie opkomende indringer spesies moet ‘n hoë proiriteit ontvang in terme van die assessering van hulle indringingspotensiaal en moontlike impakte. Geen formele studie was al gedoen oor die indringingspotensiaal van enige spesie in die genus Berberis in Suid-Afrika nie, al is dit ‘n populêre tuinboukundige genus wat al vir dekades lank gekweek word en is bekend om indringer spesies te hê. Die huidige studie het gefokus op vier sleutel punte, naamlik: 1) die toeligting van alle Berberis spp. wat in die verlede en in die hede gekweek is in Suid-Afrika, 2) die assessering van die grootte, omvang en voortplantingsouderdom van enige genaturaliseerde/indringende Berberis populasies, 3) die bepaling van potensiële bewoonbare areas van genaturaliseerde/indringende Berberis spesies en 4) om te bepaal of enige Berberis spesies amptelik gelys moet word in die Nasionale Omgewingsbestuurs Biodiversiteitswet. ‘n Totaal van 30 Berberis spesies/kultivars/hibriede was gevind om in kweking te wees gedurende die verlede sowel as die hede (11 spesies, 11 kultivars, 8 hibriede). Drie van hierdie spesies is wydverspreide indringerplante in ander dele van die wêreld, naamlik B. darwinii, B. thunbergii en B. vulgaris. Die KwaZulu-Natal provinsie het die hoogste diversiteit gehad in terme van spesies/kultivars/hibriede wat aangehou word deur kwekerye/privaat/groothandel kwekers, terwyl B. thunbergii en B. thunbergii var. atropurpurea die mees wydverspreide gekweekte spesies is. Twee indringer populasies van Berberis was gevind. Die eerste populasie was van die spesie Berberis aristata en kom voor in die Woodbush State Forest (Limpopo Provinsie; 23.8192°S 29.9608°E). Hierdie populasie het ‘n mate van voorkoms van 115 ha en ‘n area van besetting van 1.58 ha. ‘n Totaal van 5 725 individue was gegeotag en daar was gevind dat die populasies hoogs voortplantingsgereed is, meer as 40% van die populasie is alreeds in staat om te blom en saad te skiet. Die tweede populasies was van die spesie B. julianae en kom voor in die Golden Gate Hoogland Nasionale Park (Vrystaat Provinsie; 28.5049°S 28.6187°E). Hierdie populasie het ‘n mate van voorkoms van 0.42 ha en ‘n area van besetting van 0.02 ha. Die populasie is ook hoogs voortplantingsgereed, met 38% van die populasie in staat om te blom en saad te skiet. ‘n Paar geringe voorvalle van die spesie was gevind by die Alma Wildbewaarder Stasie, ook in die Golden Gate Hoogland Nasionale Park. ‘n Totaal van 473 individue van dié spesie was gegeotag. Bioklimatiese modellering het getoon dat ‘n aansieklike klomp dele van Suid-Afrika geskik is vir beide Berberis aristata en B. julianae. Die eersgenoemde spesie is meer geskik tot die bergagtige dele terwyl die laasgenoemde meer geskik is tot die sentrale dele van die land. Die situasie in terme van toekomstige klimaat (2020) was dieselfde, alhoewel ‘n reeks-inkrimping vir beide spesies gevind was. Onkruid risiko assesserings het getoon dat beide B. aristata en B. julianae ‘n voorgrens analise sou druip (telling van 27 and 22, onderskeidelik, na aanleiding van die Australiese Onkruid Risiko Assessering sisteem) en dat beide van hulle dus ‘n omgewingsrisiko is. Onkruiddoder toetse het gewys dat drie chemikalieë gebruik kan word vir die suksesvolle beheer van Berberis spp., naamlik metsulfuron-metiel, triclopyr and glifosaat. Die finale uitslag van hierdie studie is die volgende voorstelle: Berberis aristata moet gelys word as ‘n kategorie 1a indringer spesie in die Nasionale Omgewingsbestuurs Biodiversiteitswet, terwyl B. julianae gelys moet word as kategorie 1b in nie-stedelike gebiede en nie in stedelike gebiede gelys moet word nie.
Dissertation (M.Sc. (Plant Sciences (Botany))--University of the Free State, 2015
Keywords: Berberis; Invasive plants; Weeds -- Risk assessment; Invasive; Bioclimatic modelling; Weed risk assessment; Early detection; Eradication